Study on the mechanical properties of plant fiber reinforced concrete: the relationship between incorporation methods and performance - Huang, Jiawen; Zheng, Yating; Ye, Zhibin; Mao, Xi (Frontiers in Materials, 2026)
Plant fiber-reinforced concrete is gaining increasing attention due to its potential to enhance sustainability and improve mechanical properties. Among various plant fibers, reed fibers have shown promise in reinforcing concrete. However, the impact of different fiber addition sequences on the mechanical performance of concrete is not yet fully understood. This study investigates the effect of different addition sequences of reed fibers on the mechanical properties of concrete. Ordinary Portland cement was used as the base material, incorporating 0.5% by volume of 20 mm-long reed fibers. Four different addition sequences were designed: dry fiber pre-mix, dry fiber post-addition, surface-dried saturated fiber pre-mix, and surface-dried saturated fiber post-addition. Compressive strength, splitting tensile strength, and flexural strength tests were performed to evaluate the mechanical properties and strength development of concrete. The results indicate that the surface-dried saturated fiber post-addition method exhibited the optimal mechanical performance. This method improves fiber-cement particle interaction during the mixing stage, leading to a more stable interfacial bond and higher strength in compressive, flexural, and splitting tensile tests. Based on the experimental results, this study identifies surface-dried saturated post-addition as the most suitable addition sequence for reed fiber reinforced concrete, offering valuable insights for optimizing production processes and enhancing the performance of plant fiber reinforced concrete.